Seismic safety of high arch dams / Houqun Chen, Shengxin Wu, Faning Dang - Chen, Houqun
The book covers the entire subject of dam design for seismic regions, including seismic input mechanisms and modeling, non-linear analysis techniques for dam structure and foundations, concrete material properties, and simulation techniques for dam design. Of particular value are the real-world experimental data and design case studies that enhance the book and ensure that readers can apply the theoretical content to their own projects.